A low cost approach to design the tesla transformer for testing of insulating materials - Boonseng, C.; Apiratikul, P. (My University, 2001)
A high voltage with high frequency oscillation waveshape, nowadays, is used as a standard test for electrical power equipment. A Tesla transformer is one of the sources that can generate such a waveshape. This paper presents a design and a construction of a Tesla transformer used in insulator tests. The output of the transformer has a rate of 200 kV and 200 kHz. The output waveshape is controlled based on the L-C resonance circuit. The transformer is implemented for insulator tests. It is found that the accuracy of the output obtained from the Tesla transformer is in the satisfactory level.